Penggunaan Metode Card Sort pada Peningkatan Hasil Belajar Ilmu Pengetahuan Sosial - Wahyu Astuti; Elsa Putri Ermisah Syafril (Proceedings Series on Social Sciences & Humanities, 2022)
Card Sort is a collaborative activity that can be used to teach concepts, classification characteristics, facts about objects or review previously given knowledge. This method invites students to learn actively and aims to make students have an independent spirit while studying and foster creativity. Through this method, it is hoped that social studies learning that is less interesting and boring can become more interesting so that it can improve student learning outcomes according to the purpose of this study, namely to improve student learning outcomes using the card sort method. This research uses classroom action research method. The subjects of this study were students of class VIII A SMPN 1 Saptosari totaling 32 students, consisting of 16 boys and 16 girls. Data collection uses a learning outcomes test technique with 10 multiple choice questions. The results showed an increase in student learning outcomes as seen from the increase in the average score from 69.2 (pre-cycle) to 72.0 (cycle I), increasing to 74.5 (cycle II). Therefore, it can be said that the use of the card sort method can slightly add to the picture of the research problem.